PREVENTION OF ENDOMETRIAL CANCER - Agustria Z Saleh (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Endometrial carcinoma is a malignancy originating from the epithelial cells lining the uterine cavity. 1,3 Currently, endometrial carcinoma is often found in gynecological malignancies. Endometrial carcinoma is the sixth leading cause of death from malignancy in women. In Indonesia, endometrial cancer ranks third for genital cancer after cervical (cervical) and ovarian cancer. An endometrial biopsy is done to diagnose and evaluate abnormal intrauterine bleeding, t. However, in patients who cannot undergo an endometrial biopsy because of cervical stenosis or symptoms persist despite normal biopsy results, dilatation and curettage may be performed under anesthesia. Dilatation and curettage procedures are currently the gold standard for the diagnosis of endometrial cancer.2 Microscopic examination of endometrial biopsy and endocervical curettage can usually confirm the diagnosis of endometrioid or mucinous adenocarcinoma but rarely can be associated with the initial lesion of cervical adenocarcinoma in situ or atypical hyperplasia of the endometrium. The prognosis of patients with this type is poor and has a lower survival rate than patients with type 1. In addition, in some types of type 2 endometrial adenocarcinoma found an increase in molecules that are generally found in type 1, this indicates that type 2 endometrial adenocarcinoma can occur as a worsening. from the pre-existing type 1. 4 The risk of endometrial cancer is strongly associated with family history, Therefore, screening is needed as early as possible.6